130Long-term outcomes of ventricular tachycardia substrate ablation incorporating hidden slow conduction analysis. (18th June 2020) - Acosta Martinez, J; Soto-Iglesias, D; Jauregui-Garrido, B; Fernandez-Armenta, J; Penela, D; Frutos-Lopez, M; Arana-Rueda, E; Pedrote, A; Berruezo, A
Abstract: Introduction: Ventricular tachycardia substrate ablation (VTSA) incorporating hidden slow conduction (HSC) analysis allows further arrhythmic substrate identification. This study evaluates whether the analysis and elimination of HSC electrograms (HSC-EGMs) during VTSA procedures result in better short and long-term outcomes.  Methods: Consecutive patients (n = 70, 63% ischaemic, 64 ± 14.6 years) undergoing VTSA were prospectively included. Bipolar EGMs with >3 deflections and duration <133 ms were considered as potential HSC-EGM, if located within/surrounding the scar area. Whenever a potential HSC-EGM was identified, a double ventricular extrastimulus was delivered. If a local potential showed up as a delayed component, it was annotated as HSC-EGM. The incidence of HSC-EGM in core, border-zone, and normal-voltage regions was determined. Ablation was delivered at conducting channel entrances and HSC-EGMs. Procedure time, radiofrequency time, VT inducibility after VTSA and VT recurrence at 12 months after the procedure were compared with data from a historic control group (n = 66, 70% ischaemic, 65.2 ± 12 years). Results: 5076 EGMs were analyzed. 1029 (20.2%) qualified as potential HSC-EGM, and 453 of them were tagged as HSC-EGMs. Scars in patients with HSC-EGMs (n = 43, 61.4%) were smaller (39.66 ± 28.2 vs 69.4 ± 38.2 cm2; p = 0.005) and more heterogeneous (core/scar area ratio 0.24 ± 0.2 vs 0.43 ± 0.17; p = 0.03). 29.6% of HSC-EGMs were located in normal-voltage tissue; 83.5% were targeted for ablation. Patients undergoing VTSA incorporating HSC analysis needed less procedure time (213 ± 75 vs 242 ± 60 min; p = 0.018), less RF time (15.9 ± 10 vs 25 ± 12, 7 minutes; p < 0.001), had a lower rate of VT inducibility (27.5% vs 51.5%; p = 0.005) and a higher 2-year VT/VF-free survival (82.8% vs 59.7%; log rank p = 0.047) after VTSA than the historic controls . Conclusion: VTSA incorporating HSC analysis allowed further arrhythmic substrate identification (especially in normal-voltage areas) and resulted in increased  VTSA efficiency and better short and long-term outcomes.